أثر استخدام برمجيتين تعليميتين مختلفتين في تحصيل تلميذات الصف الأول الأساسي في الرياضيات (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى استقصاء أثر اختلاف نمط التدريس في برمجيتين تعليميتين في تحصيل تلميذات الصف الأول الأساسي في مادة الرياضيات. وتكونت عينة الدراسة من (41) تلميذة تم اختيارهن بطريقة قصدية، وتم تقسيم أفراد عينة الدراسة إلى مجموعتين بطريقة عشوائية: المجموعة التجريبية الأولى (21 تلميذة) تعلمت بأسلوب التعليم الخصوصي المحوسب، والمجموعة التجريبية الثانية (20 تلميذة) تعلمت بأسلوب الألعاب التعليمية المحوسبة. وأظهرت نتائج الدراسة وجود فروق دالة إحصائياً في التحصيل المباشر بين مجموعتي الدراسة ولصالح المجموعة التي تعلمت بنمط الألعاب التعليمية المحوسبة. ويوصي الباحثون بإعادة إجراء هذه الدراسة على عينة أكبر بحيث تشمل مدراس أخرى للتمكن من تعميم النتائج. This study aimed at exploring the effect of different teaching style in two instructional softwares on the first grade female students' achievement on mathematics. The subjects of the study consisted of (41) female students chosen randomly, and randomly distributed into two groups: the first treatment (21) female students learned by computerized tutorial instruction style, and the second treatment (20) female student learned by computerized instructional games. The results of the study revealed that there wear statistically significant differences on the direct achievement between the two groups in favor of the group which learned by computerized instructional games. In the light of the results the researchers recommended repeating this study by using larger samples and various instructional areas.